Molecular epidemiology of respiratory syncytial virus in hospitalised children in Heidelberg, Southern Germany, 2014-2017 - Tabatabai, Julia; Ihling, Clara Marlene; Rehbein, Rebecca M.; Schnee, Sarah Valerie; Hoos, Johannes; Pfeil, Johannes; Grulich-Henn, Jürgen; Schnitzler, Paul (Infection, genetics and evolution, 2022)
Background - Respiratory syncytial virus (RSV) is the leading cause of hopitalisation in young children with respiratory tract infections (RTI). The aim of this research project was to analyse RSV genotypes and the diversification of RSV strains among hospitalised children in Heidelberg, Germany. - Methods - We prospectively analysed nasopharyngeal swabs (NPS) from children who were hospitalised with acute RTI at the University Hospital Heidelberg, Germany, during winter seasons 2014 to 2017. RSV RT-PCR and RSV sequence analysis of the G gene coding for the attachment glycoprotein were performed. Clinical data was obtained using a standardised questionnaire. - Results - RSV was detected in 405 out of 946 samples from hospitalised children. Most RSV positive children were below the age of two years (84.4%) and had a lower RTI (78.8%). The majority of RSV positive children was male, significantly younger than RSV negative children with a median age of 0.39 years and with more severe respiratory symptoms. Out of 405 positive samples, 317 RSV strains were successfully sub-grouped into RSV subtypes A (57.4%; 182/317) and B (42.6%; 135/317). Both RSV subtypes cocirculated in all analysed winter seasons. Phylogenetic analysis of 317 isolates revealed that the majority of RSV-A strains (180/182) belonged to the ON1 genotype, most RSV-B strains could be attributed to the BAIX genotype (132/135). ON1 and BAIX strains showed a sub-differentiation into different lineages and we were able to identify new (sub)genotypes. - Conclusion - Analysis of the molecular epidemiology of RSV from different seasons revealed the cocirculation and diversification of RSV genotypes ON1 and BAIX.
Gesehen am 14.09.2022